The effects of safety certification and nutrition messaging on the demand for nutritionally enhanced food in urban Ethiopia - Jada, Kaleb Shiferaw; Melesse, Mequanint B.; Berg, Marrit van den (Springer, 2023)
Micronutrient deficiency is among the most significant public health problems in Ethiopia. In this setting, food fortification has been identified as a cost-effective and sustainable strategy to deliver essential micronutrients. Safety certification and nutrition education messages can be used to nudge people to choose fortified foods. However, there is little evidence as to the effectiveness of such interventions in this context. This paper aims to fill this gap. We focus on cooking oil, as it has been identified as an ideal candidate for vitamin A fortification in Ethiopia. To study consumers’ willingness to pay (WTP) for safety certification and vitamin A fortification, we implemented a stated choice experiment on 996 randomly selected urban consumers to reveal preferences required to calculate WTP. To estimate the causal effect of messages on consumers’ WTP for fortification, a nutrition message on the benefits of vitamin A was provided to 518 randomly selected participants. We found that consumers valued safety certification. This finding holds for certification issued by both government and private parties, with a higher value ascribed to the former. We also found that urban consumers were willing to pay a premium for vitamin A fortification. The nutrition message increased WTP for fortification, albeit only slightly. Finally, we found that the effect of safety certification on consumers’ WTP for fortified cooking oil was higher than its effect on WTP for non-fortified oil, indicating that urban consumers value certification even more when fortification is involved.